Necrose Asséptica da cabeça do fêmur - Justolin, Pedro Luis Trevizan [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Legg-Calvé-Perthes disease is a non-inflammatory aseptic necrosis of the head of the femur that is found in both young animals and humans before the gap in the femur head closes. In the fields of both human and veterinary medicine the cause of this condition is not known for certain. Various factors have been put forward in the literature as being responsible for the incidence of this condition such as: abnormalities in coagulation, changes in blood flow in the arteries, a septic obstruction in the draining of the epiphysis or the upper parts of the femur, trauma, growth cycle, hyperactivity in a child, genetic influences and dietary factors. Case histories in dogs show that the first stages of the condition progress slowly but that limping or putting weight on the limb worsens at 6 to 8 weeks. Some owners talk about a sharp onset in clinical lameness. Other clinical symptoms may include irritability, loss of appetite and knawing at the hair surrounding the affected hip. In the course of physical examination manipulating the hip joint will cause pain to the animal. The advanced stages of the disease may result in restricted amplitude of movement, muscular atrophy and fracturing. In humans the clinical signs are similar, although progression of the disease is slower so that it can be diagnosed at an earlier stage. In veterinary medicine the diagnosis is, in the main, based on case history, clinical symptoms, physical examination and certain related procedures such as radiography. The various diagnoses include physical trauma and dislocation of the medial patella. In human medicine many people have been correctly diagnosed. Whatsmore, there is a range of related procedures that are virtually not available to veterinary medicine such as magnetic nuclear resonance, that show up necroses with great clarity before radiography and cintilography do, and is considered... (Complete abstract click electronic access below)

A doença de Legg-Calvé-Perthes é uma necrose asséptica não inflamatória da cabeça do fêmur, que ocorre em animais e seres humanos jovens, antes do fechamento fisário da cabeça do fêmur. Tanto na Medicina Humana quanto na Medicina Veterinária não se sabe ao certo a causa da doença. Vários fatores foram apresentados na literatura como prováveis responsáveis dessa afecção, tais como: anormalidades de coagulação, alteração do fluxo sangüíneo arterial, obstrução da drenagem venosa da epífise e colo femoral, trauma, desenvolvimento, hiper-atividade da criança, influências genéticas e fatores nutricionais. Na anamnese os cães apresentam, claudicação com sustentação de peso que piora em 6 a 8 semanas. Alguns clientes relatam o início agudo da claudicação. Outros sinais clínicos podem incluir irritabilidade, diminuição do apetite e mastigação da pele sobre o quadril afetado. No exame físico a manipulação da articulação coxofemoral desencadeia dor. Limitação da amplitude de movimentos, atrofia muscular e crepitação podem estar presentes na doença avançada. Em humanos os sinais clínicos são semelhantes, porém como a evolução é mais lenta o diagnóstico pode ser feito mais precocemente. Na medicina veterinária o diagnostico é realizado basicamente pela anamnese, sinais clínicos, exames físicos, e complementares (radiografia). Os diagnósticos diferenciais compreendem: trauma fiseal e luxação de patela medial. Na medicina humana os casos também são diagnosticados com sucesso; entretanto, existem exames complementares que na Medicina Veterinária são menos acessíveis: a ressonância nuclear magnética, que demonstra com clareza a necrose antes da radiografia; e a cintilografia, considerado o principal meio para diagnóstico precoce. O tratamento atual da necrose asséptica da cabeça do fêmur... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Femur - Doenças; Femur - Necrose; Cão; Femur - necrosis